(untitled) (Педагогіка вищої та середньої школи, 2010)
Problem offorming of category scientific vehicle which relates by organization of the interactive teaching is described in this article. Interpretation of concepts "interactive teaching", "interactive technologies", "interactive methods" is offered by author.